Microwave Ablation Versus Nipple Sparing Mastectomy for Breast Cancer ≤5 cm: A Pilot Cohort Study - Yu, Jie; Han, Zhi-yu; Li, Ting; Feng, Wen-zhe; Yu, Xiao-ling; Luo, Yan-chun; Wu, Han; Jiang, Jian; Wang, Jian-dong; Liang, Ping (Frontiers in Oncology, 2020)
OBJECTIVES: Compared with nipple sparing mastectomy (NSM), microwave ablation (MWA) is one relatively new modality indicated for selected breast cancer with nipple sparing, and with little of evidence-based medical research for decision-making. The objective of this study was to compare the effect of ultrasound-guided percutaneous MWA and NSM for breast cancer. MATERIALS AND METHODS: A retrospective cohort study was conducted in a single institution from 2014 to 2020. Women with invasive ductal carcinoma of the breast ≤ 5 cm treated by MWA or NSM were enrolled. The primary end point was tumor progression in the intention-to-treat population. Secondary end points included survival, cosmetic results, and complications. RESULTS: 21 patients in MWA group and 43 in NSM group were evaluated. The mean tumor size was 2.3 cm (range, 0.3-5.0 cm). Median follow-up was 22.7 months (range, 10.6–58.5 months). The mean age of MWA was 24 years older than that of NSM group. All the patients achieved technique effectiveness. One local tumor progression and one ipsilateral breast recurrence occurred at 42 and 28 months after MWA, respectively. One ipsilateral breast recurrence and one bone metastasis occurred at 31.2 and 34 months after NSM. Two groups had no significant difference in tumor progression (P = 0.16). No participants in both groups developed cancer related death (P > 0.99) and major complications (P > 0.99). However, MWA needed less hospitalization time (P<0.001) and achieved better cosmetic results (P < 0.001). CONCLUSIONS: MWA achieved similar short term effect for breast cancer control and better cosmetic satisfaction compared with NSM in selected patients. And MWA provides appropriate option for elderly patients who are unfit for surgery.